Leveraging religious identity: Anies Baswedan’s political strategy in the 2024 Indonesian Presidential Election - Al-Fikri, Muchsin; Truna, Dody S.; Nurdin, Ahmad Ali (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
This article investigates the dynamics of religious identity politics in Indonesia’s 2024 presidential election, with a particular focus on the political communication strategy of Anies Rasyid Baswedan. The study aims to explore how religious narratives and symbols are constructed within Anies’s campaign discourse and to examine the broader socio-political implications of such identity-based appeals in a pluralistic democracy. Employing a qualitative phenomenological approach, the research analyzes a range of data, including media coverage, campaign speeches, symbolic visual elements, and relevant literature. The findings reveal that religious identity politics has not vanished from Indonesia’s electoral landscape but has undergone a strategic transformation. Rather than employing overt sectarian messaging, Anies leverages a symbolic, layered communication strategy that harmonizes his personal religious image with themes of national unity, moral leadership, and cultural pluralism. This enables him to appeal simultaneously to conservative Muslim constituencies and urban moderate voters. His approach reflects a shift from the confrontational identity politics of previous elections toward a more adaptive and communicative form of religious symbolism. In conclusion, this study shows that identity politics in contemporary Indonesian elections is increasingly mediated through symbolic discourse and nuanced messaging. The research contributes to a deeper theoretical understanding of the evolving role of religious identity in electoral democracies and offers practical insights into the ethical and strategic dimensions of political communication in a culturally diverse society.